INFLUENCE OF THE APPLICATION OF DESICCATION IN THE PHYSIOLOGICAL QUALITY OF SOYBEAN SEEDS - Santos, F. L.; Bertacine, F.; Souza, J. S.; Simões, I.; Bossolani, J. W.; Sá, M. E. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Brazil is the second largest producer of soybeans in the world, where more and more quantities and quality of this legume has been demanded. The application of desiccants that allows anticipation of harvesting in seed production areas has been used to minimize quality losses. Therefore, the objective of this work was to analyze different cultivars of soybean in influence of the application or not of desiccant in function of the physiological quality of the seeds. The experiment was conducted in the Laboratory of Seed Production and Technology with Experimental Design Completely Randomized (DIC) arranged in a factorial scheme (4x2) with 4 replicates. The treatments consisted of four soybean cultivars: CD 2728 IPRO, SYN 1366C IPRO, BRS 7380 IPRO, BRS 7470 RR with and without desiccant application. Tests of germination, accelerated aging, germination speed index, electric conductivity, vigor classification of seedlings, fungal infestation on germination and dry mass of seedlings were performed. The use of desiccant negatively influenced the physiological quality of soybean seeds, with the exception of cultivar BRS 7380 RR.